Pembelajaran Tari Kreatif Melalui Stimulus Lagu Daerah - Yusup, Ujang Maulana (CV. ITTC INDONESIA, 2024)
This article aims to discuss regional songs as a stimulus in learning creative dance. Starting from the development of curriculum demands that require students to have various skills. Creative dance learning is a learning concept that gives students the freedom to develop their creative potential. This article is analyzed by comparing the concept of creative dance with other creative dance concepts as well as through the results of several previous studies. The issues that will be discussed in this article are the concept of creativity, the concept of creative dance learning and the concept of folk songs as a dance stimulus. Through the stimulus of regional songs, it is hoped that it can provide space for self-expression for students in learning creative dance.